Pengaruh Metode Mustaqilli Terhadap Pemahaman dan Kemahiran Bahasa Arab Siswa MTs Al-Islam Nganjuk - Trianingsih, Feni; Khoiruddin, M. Arif (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
This study aims to determine the effect of the mustaqilli method on the understanding and proficiency of the Arabic language of MTS Al-Islam Nganjuk students. This research used interviews, observation, documentation, questionnaire, and test methods. At the same time, data analysis uses quantitative techniques with bivariate analysis. Bivariate analysis is applied because the variables analyzed consist of two kinds, namely dependent and independent. The statistical test used in this study is the Chi-Square test, while to test hypotheses 1, 2, and 3, the N-Gain Score test and the T-test are used. The results of this study indicate that the Arabic language learning process using the Mustaqilli method obtained data for class 1 by 26.4%, class 2 by 27.7%, and class 3 by 27.7%. Student motivation and teacher attention obtained data of 63.7%, class 2 of 60.4%, and class 3 of 57.6%. It concluded that 90.40% of respondents responded positively to learning Arabic using the Mustaqilli method. The pretest and post-test data of students in Control and experimental classes showed that in class 1, the ability and proficiency of the Arabic language of MTS Al-Islam using Control (Lecture) was 40% rated ineffective, and 60% rated less effective. While using the Experiment (Mustaqilli), 40% rated it adequate, and 60% very effective. For class 2 using Control (lecture), 10% rated ineffective, 70% were less effective, and 20% were quite effective. While using experiments (Mustaqilli), 20% were effective, and 80% were very effective. For Class 3, using Control (lecture) 100% is less effective, while the experiment (Mustaqilli) 30% is quite adequate, and 70% is very effective.